Respostas induzidas pelo exercício resistido sobre o perfil hematológico de ratos wistar tratados com dexametasona - Abbehusen, Luciana de Freitas (2018)
Introduction: Glicocorticoides are pharmacos utilized in treatment of inflamatory diseases. However, they can trigger adverse reactions that can compromise the immune system and metabolism. Physical exercise can be used as a non pharmacologial way to minimize these effects. Objective: To evaluate the responses induced by resisted exercise over hematological profile of rats treated with dexametasona. Methods: 40 rats were used for the study and divided into 4 randomized: sedentary control (SC), trained control (TC), sedentary dexamethasone (SDx), and trained dexamethasone (TDx). The groups were subjected to resistance exercise for 12 weeks. three series of 10 repetitions, with intensity of 70% - 1RM), in a squatting apparatus. Dexamethasone (0.2 mg / kg) was given intraperitoneally once weekly. After 24 hours of the last training session, the animals were euthanized for sample collection. The statistical test used was ANOVA One Way, with Bonferroni post-test and data were expressed as mean ± standard error (SEM) with p <0.05. Results: The mean corpuscular hemoglobin concentration (MCHC) decreased in SDx (3.4%) and TDx (3.6%) groups compared with the TC group. The number of total leucocytes increased in the TC group compared with SC (24.3) and SDx (37.8%) groups. The number of neutrophils in the SDx group increased compared with SC (50.0%) and TC (41.9%) groups. The number of lymphocytes decreased in the SDx group compared with the SC (31.4%) and TC (26.9%) groups. The number of monocytes decreased in the SDx group compared with the SC (46.1%) and TC (47.9%) groups. Conclusion: The resistance exercise was unable to attenuate the effects of dexamethasone on the MCHC, neutrophil, lymphocyte, and monocyte levels.